The use of stereotactic body radiation therapy for local control of glomangiomatosis: a case report - Horne, Zachary D.; Karam, Sana D.; Snider, J W.; Rashid, Abdul; Lax, Allison; Ozdemirli, Metin; Harter, K William (Frontiers in Oncology, 2013)
The vast majority of glomangiomas are small, benign neoplasms that can occur anywhere in the body but typically arise in the subcutaneous tissues of the extremities and are capable of causing extreme pain. Typically, these lesions are managed surgically with excellent rates of tumor control. On occasion, patients present with a variant of the glomangioma tumor consisting of numerous or recurrent nodules, a condition classified as glomangiomatosis. The authors present a case report of a young patient with multiply recurrent painful glomangiomas of the left foot, who was ultimately diagnosed with glomangiomatosis pedis. After multiple surgeries and surgical consultations, no surgery other than amputation was recommended. Therefore, the patient sought consultation with regard to stereotactic body radiation therapy (SBRT). In the absence of other options, and based on its effectiveness in treating glomus tumors of the head and neck which display similar natural history and histologic features, SBRT was offered. The patient underwent SBRT to the largest of his remaining tumors with excellent local control and significant reduction in pain at two and a half years follow-up.